2022
DOI: 10.1186/s12876-022-02603-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of circulating tumor cell-white blood cell clusters with survival outcomes in patients with colorectal cancer after curative intent surgery

Abstract: Background The analysis of circulating tumor cell-associated white blood cell (CTC-WBC) clusters represented the progress in the liquid biopsy of malignant tumors, however, related research in patients with colorectal cancer is still absent. Methods To explore associations between CTC-WBC clusters and the prognosis of these patients, we conducted an independent cohort of 329 colorectal cancer patients after curative intent surgery and pre-operative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Prospective studies, as represented by Jansson et al [ 16 ] and Zhu et al [ 20 ], showed a significant association of CTC-WBCs with OS (HR = 11.44, 95% CI: 2.71–48.37, P = 0.001, Table 3 ). The retrospective studies [ 10 , 11 , 18 , 19 ] also demonstrated a notable association with OS (HR = 2.55, 95% CI: 1.78–3.63, P < 0.001, Table 3 ). For disease progression endpoints, the prospective group reported an HR of 1.31 (95% CI: 0.46–3.75, P = 0.609).…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…Prospective studies, as represented by Jansson et al [ 16 ] and Zhu et al [ 20 ], showed a significant association of CTC-WBCs with OS (HR = 11.44, 95% CI: 2.71–48.37, P = 0.001, Table 3 ). The retrospective studies [ 10 , 11 , 18 , 19 ] also demonstrated a notable association with OS (HR = 2.55, 95% CI: 1.78–3.63, P < 0.001, Table 3 ). For disease progression endpoints, the prospective group reported an HR of 1.31 (95% CI: 0.46–3.75, P = 0.609).…”
Section: Resultsmentioning
confidence: 83%
“…Qiu et al [ 18 ] identified a noteworthy association of CTC-WBCs with OS in GC (HR = 2.553, 95% CI: 1.008–6.465, P = 0.048). Xu et al [ 19 ] observed a similar trend for PFS in CRC (HR = 1.89, 95% CI: 1.02–3.51, P = 0.042), though the OS association was not significant. Additionally, Zhu et al [ 20 ] found that in SCLC, CTC-WBC clusters were a significant prognostic factor for OS both before treatment (HR = 9.3, 95% CI: 1.4–48, P = 0.0079) and after two chemotherapy cycles (HR = 4.4, 95% CI: 1.1–18, P = 0.041), highlighting their consistent prognostic value regardless of treatment stage.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations